Assessment of Production and Marketing of Camel Milk in Khartoum State (Journal of Veterinary Medicine and Animal Production, 2022)
This study aimed to investigate the economics of production and marketing of camel milk in Khartoum State, Sudan focusing on factors affecting the production and marketing of camel milk. Primary data were collected by means of a questionnaire using a stratified random sample of 30 herdsmen, 30 marketing centers and 30 consumers, selected from Khartoum State. The secondary data were collected from different related sources of information. The collected data were analyzed by descriptive statistics and budgetary analysis. Descriptive statistical analysis result revealed that the socioeconomic characteristics of the herdsmen were more or less homogenous as about 84% of the herdsman shared the same socioeconomic characteristics. The results showed that the cost of feeding constitutes the highest proportion of the total cost of milk production. Also, the results indicated that the most important factors affecting the marketing of camel milk were high milk prices (43.3% of the sample of milk consumers), remote camel milk marketing centers from consumers (40% of the sample) and low camel milk production (16.7% of the sample). Budget analysis results showed that the average total variable cost of production for camel milk was found to be about SDG 1.090 per pound. The breakeven shows that the percentage of income before taxes equals SDG 5.000 (28.1%) of total sales. The taxes percentage is calculated at 1.8%. Hence the net income percentage is 26.4%, which equals SDG 4.910. The result revealed that the business was profitable at camel milk producers’ level in Khartoum State. The quantity of milk that should be produced to recover the cost for each she camel is calculated according to the same formula is 1.09 pounds. The study recommended availing extension services and feed concentrate rations for camel milk producers, increasing the number and locations of camel milk selling centers and increasing the awareness of the consumers on the medicinal and nutritional values of camel milk.